Peningkatan Keterampilan Membaca Nyaring Melalui Media Cerita Bergambar Di Kelas Rendah - Gina Purwati; Dyah Lyesmaya; Iis Nurasiah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
Research through pictorial story media aims to improve the learning process of loud reading skills in the low class. This type of research is classroom action research (CAR). The number of students studied in this study was 26 students consisting of 15 men and 11 women. The instruments used in this study consisted of observation sheets of teacher and student activities, attitude assessment sheets and tests. The results showed the activities of teachers in the first cycle obtained an average value of 60 with good categories, the second cycle obtained an average score of 92 with a very good category and the activities of students in the first cycle obtained an average value of 62 with good categories, cycle II obtained the average value of 81 with a very good category while the reading skills through pictorial story media in the pre-cycle activities obtained a percentage of 62% with good categories, in the first cycle obtained a percentage of 64% with good categories, then in the second cycle increased by 88% by category very good. based on the results obtained it can be concluded that the use of pictorial story media can improve the loud reading skills of students in the lower classes.